Investigation into the Use of Macroporous Anion Exchangers for the Sorption and Separation of Iminodiacetate Complexes of Lanthanum(III) and Neodymium(III) - Halina Hubicka; Dorota Kolodyńska (Adsorption Science & Technology)
Rare earth element complexes with iminodiacetic acid (IMDA) of the Ln(IMDA) − 2 type exhibit an unusual sequence of affinities for anion exchangers. In this work, the applicability of strongly basic gel and macroporous polystyrene anion exchangers to the sorption and separation of rare earth element complexes with iminodiacetic acid has been investigated. It was shown that the acetate forms of both the macroporous and gel anion exchangers were most effective and cheapest for this type of separation. As far as their applicability to the purification of lanthanum(III) IMDA from the corresponding neodymium(III) complexes is concerned, the anion exchangers investigated may be arranged in the following sequence: strongly basic gel anion exchangers ≈ strongly basic macroporous anion exchangers > weakly basic macroporous anion exchangers.